Zapomniana twórczość dramatyczna Bolesława Eulenfelda (1848–1918) (Heteroglossia – studia kulturoznawczo-filologiczne, 2023)
This article falls into the trend of restoring the memory of the so-called creators of minorum gentium, that is, „smaller format”. It contains basic biographical information which was obtained through the inquiry, concerning the forgotten Lviv writer Bolesław Eulenfeld, as well as a literary sketch of his work, along with its reception at the time (and contemporary). During his lifetime, Eulenfeld was an extremely prolific and popular playwright in Galicia, children’s literature writer, and even an actor for several years. Today he is mentioned rarely, hardly ever, so we decided to bring his profile closer and restore the memory of him.